Protein-Protein Interaction Network Analysis and Drug Repurposing for Uveal Melanoma Patients: Drug Repurposing for Uveal Melanoma - Sadat Soleimani Zakeri , Negar; Tabrizi-Nejhadi, Parinaz; Abbasi, Amirreza; MotieGhader, Habib (Journal of Ophthalmic and Optometric Sciences, 2020)
Background: Uveal melanoma is the most prevalent melanoma in adults. This malignancy arises from melanocytes. Patients with uveal melanoma were investigated according to their metastases and non-metastases status to propose candidate drugs. Material and Methods: The studied data set included 63 patients (24 females and 39 males), among whom 35 patients were with metastases and 28 patients were without metastases. By comparing the metastases and non-metastases cases, 2000 genes were chosen as practical genes. A co-expression network was constructed, and protein complexes were extracted to find effective gene modules. Then drug-gene networks were constructed to find essential drugs. Results: The STRING database was utilized to construct a co-expression network. Then, protein complexes were extracted using the MCODE clustering algorithm. Four meaningful modules were chosen for the next step. Afterward, drug-gene subnetworks were constructed and illustrated, and high degree drugs were chosen as effective drugs for this disease. Conclusion: As a result, 12 important drugs were introduced as the proposed candidate drugs. By detailed investigation of the obtained results, drugs that were not previously reported were introduced as new drugs, which would be studied experimentally in future works. These were Bortezomib, Oprozomib, Clofarabine, ME-344 and NV-128.